OP0054 Safety and Efficacy of Subcutaneous Tocilizumab in Adults with Systemic Sclerosis: Week 48 Data from the Fasscinate Trial. (9th June 2015) - Khanna, D.; Denton, C.P.; Jahreis, A.; van Laar, J.M.; Cheng, S.; Spotswood, H.; Pope, J.E.; Allanore, Y.; Müller-Ladner, U.; Siegel, J.; Furst, D.E.
Abstract : Background: Systemic sclerosis (SSc) is a debilitating disease with limited treatment options. Data indicate a key role for interleukin-6 (IL-6) in the pathogenesis of SSc. 1, 2 In murine models of SSc, IL-6 receptor (IL-6R) inhibition prevented and reversed skin fibrosis. 3, 4 Objectives: To assess safety and efficacy of the IL-6R inhibitor tocilizumab (TCZ) in pts with SSc. Methods: In this first double-blind, placebo-controlled, phase 2, proof-of-concept study, the effect of inhibiting IL-6 in SSc was explored. Pts ≥18 y with active SSc (1980 ACR criteria, 5 ≤5 y disease duration, modified Rodnan skin score (mRSS) 15-40, and elevated acute-phase reactants) were randomized 1:1 to TCZ 162 mg or placebo (PBO) subcutaneously (SC) wkly for 48 wks. Primary end point was mean change in mRSS from baseline at wk 24. Mean change in mRSS at wk 48, pt-reported outcomes (PROs), and pulmonary function at wk 48 were secondary/exploratory measures. Results: 87 pts (43 TCZ, 44 PBO) were enrolled. Baseline characteristics were similar between arms including mean [SD] mRSS (TCZ 26 [7.2]; PBO 26 [5.9]). At wk 24, a favorable but not statistically significant effect of TCZ over PBO on mRSS was noted (–3.9 vs –1.2; adjusted mean difference, –2.7 [95% CI: –5.85, 0.45], p =0.09; Table ). At wk 48, a numerically larger change was noted in the TCZ vs PBO arm (–6.3 vs –2.8; adjusted mean difference, –3.6 [95% CI: –7.23, 0.12], p =0.06). Though not statistically significant, higher proportions of TCZ vs PBO pts had mRSS improvement from baseline of ≥20% (40% vs 27%), ≥40% (21% vs 7%), or ≥60% (12% vs 0). There were numerically greater improvements in the TCZ arm than in the PBO arm for PROs (HAQ-DI, pt global assessment VAS, and FACIT-fatigue) at wk 48 (Table ). The proportion of pts with HAQ-DI improvement ≥0.22 was 28% (12/43) in the TCZ arm and 7% (3/44) in the PBO arm at wk 48 ( p =0.01). Fewer TCZ vs PBO pts showed a decline in % predicted forced vital capacity (%FVC <0; 57% vs 84%) and a >10% absolute decrease in %FVC (10% vs 23%; Table ) at wk 48. Adverse events (AEs)/serious AEs occurred in 98%/33% of TCZ and 91%/34% of PBO pts by wk 48. One death occurred in the PBO arm and 3 deaths in TCZ pts by wk 48; all were unrelated to study drug except for a fatal lung infection in 1 TCZ pt. Conclusions: Treatment with TCZ resulted in consistent, but not statistically significant, improvements in skin sclerosis (mRSS) at wks 24 and 48 and in PROs (HAQ-DI, pt global assessment VAS, and FACIT-fatigue) at wk 48. A trend toward less FVC decline with TCZ than with PBO noted at wk 24 persisted at wk 48. Observed AEs were consistent with SSc complications and the safety profile of TCZ. Overall, the effect of TCZ on skin sclerosis, PROs, and pulmonary function and the observed safety profile suggest a positive risk/benefit profile for TCZ in SSc and support further evaluation of TCZ in pts with SSc. References: J Rheumatol 1998;25:308. Pathobiology 1993;61:239. Am J Pathol 2012;180:165. Arthritis Rheum 2014:66:S1312. Arthritis Rheum 1980;23:581. Disclosure of Interest: D. Khanna Grant/research support from: Actelion, Bayer, BMS, EMD Seerono, Gilead, InterMune, NIH/NIAMS, NIH/NIAID, Scleroderma Foundation, Pulmonary Hypertension Association, Consultant for: Actelion, Bayer, BMS, EMD Serono, InterMune, Biogen Idec, Genentech/Roche, Cytori, Lycera, Sanofi-Aventis/Genzyme, GSK, C. Denton Grant/research support from: Roche, Novartis, Consultant for: Roche, Actelion, GlaxoSmithKline, A. Jahreis Shareholder of: Roche, Employee of: Genentech, J. van Laar Consultant for: Pfizer, Tigenix, Novartis, Roche, Eli Lilly, S. Cheng Employee of: Genentech, H. Spotswood Shareholder of: Roche, Employee of: Roche, J. Pope: None declared, Y. Allanore Grant/research support from: Actelion, BMS, Genentech/ Roche, Inventiva, Pfizer, Servier, Consultant for: Actelion, Bayer, Biogen Idec, BMS, Genentech/ Roche, Inventiva, Medac, Pfizer, Sanofi/Genzyme, UCB, U. Müller-Ladner Consultant for: Roche, Chugai, Speakers bureau: Roche, Chugai, J. Siegel Employee of: Roche, D. Furst Grant/research support from: Genentech, Consultant for: Genentech